Comparison of Methods for Computing Highly Accurate Daily GNSS Positions - Sergey Kuzikov; D. V. Kenigsberg; Yuliya Salamatina; O. A. Prokhorov (Civil Engineering Journal, 2023)
In Central Asia, the level of geodynamic displacements of the Earth's crust does not significantly exceed the accuracy of their measurement methods. Therefore, we need to choose the most accurate methods of calculating coordinates for cosmogeodetic stations. In this work, based on the data of 8 days of GPS measurements at 10 stations, 7 sets of average daily geocentric XYZ coordinates were calculated using different methods. To determine the positions, we used 3 calculation methods in the GAMIT/GLOBK program, 2 methods in the Bernese GNSS software, and 2 web services. To estimate the differences between 7 coordinate sets, we used parameters based on the Euclidean distance between these coordinate samples. The difference analysis of all pair combinations for 7 coordinate sets was carried out by 3D radius vectors, individual coordinate axes, and individual observation stations. The calculations showed that the positioning accuracy and precision depended not only on the coordinate calculation method but also on the selected reference frame. Methods using the international terrestrial reference frame (ITRF) provide station positions with regular deviations of <2 mm and individual deviations up to 5 cm. Methods using the regional and "point" reference frames have regular discrepancies for individual coordinates up to 2 cm and maximum deviations up to 1 m. Converting XYZ coordinates to UVW with the local reference frame reduces the difference between UVW sets by at least 25%. Due to the spatial orientation relative to the studied stations, the X (U) coordinate is reproduced 2-3 times with smaller deviations than other coordinates. The average deviation level of coordinate sets can be an indicator of the quality of conditions for receiving a GNSS signal at one station. We have identified the station group that has a coordinate deviation level several times lower than other stations. Doi: 10.28991/CEJ-2023-09-02-04 Full Text: PDF